The Discrimination between husband and wife in the lawsuit of dissolution on the marriage contract on the cause of madness -legal jurisprudence study- - Zagzoog, Nedaa; Snobar, Nour (Jordan Journal of Islamic Studies, 2023)
This study addresses the concept of dissolution on the marriage contract on the cause of madness, and the legitimacy of jurisprudential regarding this matter, and the work of the Jordanian legislation, and the legal consequences that impacts the dissolution of the marriage contract on the cause of madness, and who has the right to call on the dissolution on the cause of madness in the Jordanian Sari'e courts of law. This study also shows the debate of the likelihood of the Jordanian legislator on having the right to request the dissolution on the cause of madness how it favors the wife not the husband and on one side how convenient this likelihood is, on the other hand on the principals of justice. This study came to a number of conclusions, the most significant ones are: the Jordanian legislator took the jurisprudential opinion that granted the wife the right to request the dissolution of the marriage contract on the cause of madness and not for the husband, which is the preponderant view in Al Malki jurisprudential, and this likelihood is for the benefit of the greater good in the eyes of the legislator. However, this study also worked towards discussing this legislation and recommended equal treatment in dissolution on the cause of madness between the man and the woman.